Tautomated Colorectal Lymphoma Volume Calculation Using 3d Mri Images - Manu M R, Dr. B Balamurugan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The third most prevalent cause of cancer death in the world is colorectal lymphoma (CL). Future disease burden predictions advise health planners and raise awareness about the need for action on cancer control. The lymphoma volume is usually estimated by means of magnetic resonance imaging (MRI), which analyses mutation during medical diagnosis at advanced stages. The precise segmentation of abnormal tissue and its correct 3D display is key to appropriate treatment. Here, there is an intention to build a smart diagnostic system based on the human MRI research. The suggested model presenting identification, Segmentation and 3D visualization method, offering medical specialists’ expertise an efficient way for the 3D reconstruction of colorectal lymphoma using medical image processing in two-dimensional magnetic resonance images. Here the rectal MR images are Preprocessed that can be done using the weighted adaptive median filtering and uplift laplacian partial differential equation for further enhancement. Followed by preprocessing the Iterative Multi-linear component analysis was used for extracting the features. The extracted features can be given as an input for the CNN based Multiscale phase level set segmentation process. In this suggested segmentation, the abnormal resection margin is automatically analyzed and shows that this is consistent with traditional segmentation algorithm. Finally, a 3D simulation of the lymphoma of the colon is accomplished using the logical frustum model used for medical data rendering. The feasibility of the method suggested is confirmed by the 98.7% accuracy of the Colon MRI dataset. A subjective comparative analysis between the proposed approach and other state of art methods is also carried out as out in the work mentioned. The findings of experiments show a higher performance of the system than conventional systems, which support radiologists in measuring lymphoma size, structure and position in the colon.